Technology to save the resource of Pt-catalyst for higher paraffins dehydrogenation - Frantsina E. V. Evgeniya Vladimirovna; Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Kozlov I. A.; Andreev A. B.; Platonov V. V.; Belinskaya N. S. Natalia Sergeevna; Glik P. A. Pavel Andreevich (2016, 2016)
Title screen